Analysis of factors affecting outcome in pediatric omphalitis - Jayaswal, Shalika; Shah, Hemanshi; Kumbhar, Vikrant (International Surgery Journal, 2016)
Background: Omphalitis is inflammation of the umbilical cord stump. Omphalitis contributes to neonatal morbidity and mortality. Methods: A prospective study of retrospective data of 25 children with umbilical swelling, redness and discharge was analyzed for age of presentation, home delivery versus institutional delivery, cord clamping and cutting practices, local applications, microbiological swab, management and complications. Results: Common symptoms were umbilical swelling, erythema and sero-purulent discharge. Four neonates had a home delivery. Most common organism isolated was Staphylococcus aureus. 14 patients responded to intravenous antibiotics and daily dressing. 11 patients required surgical intervention. Conclusions: Institutional delivery, cord cutting and cord care practices reduces the frequency of omphalitis. Uncomplicated omphalitis resolves without significant morbidity. Early diagnosis and treatment reduces the risk of complications.